Gefitinib encapsulation based on nano-liposomes for enhancing the curative effect of lung cancer. Issue 24 (16th December 2020) - Hu, Yanjie; Zhang, Jisong; Hu, Huihui; Xu, Shan; Xu, Li; Chen, Enguo
ABSTRACT: Gefitinib (GEB) is one of the drugs used for patients with epidermal growth factor receptor (EGFR)-positive mutations in non-small cell lung cancer (NSCLC). However, application of GEB is limited by its low water solubility, stability, and utilization rate, especially the side effects while GEB is given by oral. In this study, nanoliposome was used as a carrier to prepare nanoliposome compound drug (GL) by embedding GEB in the nanoliposome perfectly combined with green nontoxic solvent and thin-film dispersion method. The nanoliposome structure was expected to improve the water solubility and biocompatibility of GEB, thus improving the effect of cancer treatment. The surface electronegative nanoliposomes can effectively avoid protein adsorption and prolong the circulation time in vivo . Meanwhile, the ratio of lecithin to cholesterol (LE/CH) was explored to maximize the encapsulation efficiency of nanoliposome. Subsequent test results showed that GL exhibited better stability, smaller particle size and higher encapsulation efficiency. In addition, in vitro drug release curve also further confirmed that GL had a promising drug sustained-release effect. In particular, a series of in vitro tests such as cell activity, apoptosis, colony formation, scratch, invasion, and cell cycle assays were performed. The results indicated that GL significantly enhanced the pro-apoptotic effect on A549 cells. Most cell cycles of A549 cells were blocked in the G0/G1 phase influenced by GL, thus inhibiting the proliferation of cancer cells. In vivo anti-tumor studies showed that compared with pure GEB, GL had a significant inhibiting effect on NSCLC. In conclusion, the GL which was synthesized by a simple method in this study significantly improved the treatment effect of cancer cells, which proved that the nanoliposome carrier had an excellent application prospect in the treatment of lung cancer.